PENGUKURAN TINGKAT STRES MAHASISWA BERDASARKAN GENDER: APLIKASI IMPOTANCE PERFORMACE ANALYSIS - Anfas, Anfas; Buamonabot, Irfandi; Umasugi, Mohbir; Sudarwo, Raden (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
This study aims at investigating gender based students’ stress pattern at Regional office of  Ternate. The respondents of this study were 160 students of Faculty of Economy in At regional office Ternate  consisting 40 male respondents and 40 female respondents of Management study program, and 40 male respondents and 40 female respondents of Accounting study program. To gather the data, a survey method was employed. Data was analyzed by using Importance Performance Analysis. The results showed that nothing was recommended for improvement atthe Regional office of Ternate economic faculty.